A retrospective study on ectopic pregnancy: incidence, clinical presentation, risk factors, treatment and morbidity and mortality associated with ectopic pregnancy- one year study - Godria, Payal P.; Darda, Medha G.; Modi, Dipti A.; Rami, Bijal D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Diagnosis of ectopic pregnancy was frequently missed and rising trend in incidence of ectopic pregnancies necessitates awareness about risk factors, resultant morbidity and mortality. to determine the incidence, clinical presentation, risk factors, treatment and morbidity and mortality associated with ectopic pregnancy. Aims and Objectives were to determine the incidence, clinical presentation, risk factors, treatment and morbidity and mortality associated with ectopic pregnancy. Methods: Retrospective analysis of ectopic pregnancy was done in Government Medical College Baroda, from September 2021 to August 2022. The following parameters: age, parity, gestational age, risk factors, clinical presentation, diagnostic methods, mode of treatment and morbidity were noted. Results: Out of 7521 deliveries, 74 were ectopic pregnancies (0.98 %). Women with age 20-30 years had highest incidence (62.16%) and with least below 20 years (4%). Ectopic pregnancies were common in multiparous women (78.3%) than primigravida (21.62%). Common symptoms: abdominal pain (82.4%), amennorhea (78.4%), bleeding per vaginum (63.3%), adenexal tenderness (46.2), asymptomatic (12%) patients. Urine pregnancy test positive in 96.4%. Etiology was pelvic infection (15.78%), infertility (7.01%), previous ectopic (8.33%), contraception failure (8.71%), surgeries including LSCS and tubal surgeries (4%). Right sided ectopic was more common. Site of ectopic was common in fallopian tube- ampullary region (88%), cornu (4%) followed by others (8%) then caesarean scar, rudimentary horn pregnancy. About 81.08% of ectopic was ruptured, 3/4th of these patients presented with shock at the time of presentation. Tubal abortions were seen in 4.01% of patients. Most of cases being ruptured ectopic pregnancies, salpingectomy in 72.9% and salpingo-opherectomy in 6.7%. Morbidity was blood transfusion (76.31%), wound complications 4.38 and no mortality. Conclusions: Early diagnosis, identifying of underlying risk factors and timely intervention in the form of conservative or surgical treatment will help in reducing the morbidity and mortality associated with ectopic pregnancy.